The UAE and foreign policy : foreign aid, identities and interests - Almezaini, Khalid S. (Milton Park, Abingdon, Oxon : Routledge, 2012)
'This book provides a detailed analysis of the foreign policy and foreign aid strategies of the United Arab Emirates (UAE). Exploring the cultural factors that have impacted on the foreign policy behaviour of the UAE and its foreign aid, the author argues that the country's foreign policy and foreign aid is strongly influenced by Islamic teachings and by its Arab culture. The author offers a critical analysis of Arab aid in general through the lens of International Relations theories (mainly Constructivism and Rationalism), as well as an in-depth study of the UAE's foreign aid programme. Using the case studies of Palestine and Pakistan, the focus moves beyond the UAE to show how cultural factors have impacted on the behaviour of the authorities across the wider Arab Middle East.Adopting a new approach to how this particular case is examined and researched, this book will be of particular interest to students, researchers and academics interested in Middle East studies, the Gulf States, Middle East politics, and foreign aid and foreign policy'--
'This book offers a concise and detailed analysis of the United Arab Emirates (UAE) foreign aid as a main instrument in its foreign policy. Exploring the cultural factors that have impacted on the foreign policy behaviour of the UAE and its foreign aid, the author argues that Arabism and Islamic traditions have shaped the country's foreign policy in general and foreign aid in particular. Examining in depth the motives and purposes of this large aid program through the lens of International Relations theories (mainly Constructivism and Rationalism), the book details the UAE's foreign policy and aid program since its inception. Drawing on a comprehensive analysis of two major recipients of aid from the UAE - Palestine and Pakistan - the focus moves beyond the UAE to show how cultural factors have impacted on the behaviour of the authorities across the wider Arab Middle East. This critical assessment and analysis of the UAE's foreign policy will be of particular interest to students, researchers and academics interested in Middle East studies, the Gulf States, Middle East politics, and foreign aid and foreign policy'--
Includes bibliographical references (p. [164]-170) and index.
Keywords: Economic assistance, Emirati; United Arab Emirates -- Foreign relations; United Arab Emirates -- Foreign relations -- Arab countries; United Arab Emirates -- Politics and government